2021
DOI: 10.1002/jdd.12741
|View full text |Cite
|
Sign up to set email alerts
|

Assessing grit as a potential additional domain for dental students' selection

Abstract: Background: Unhappiness, stress, and burnout will often lead to low academic performance among dental students. Perseverance and passion for long-term goal, known as grit, could overcome these despondent emotions. Our Study is looking at whether grit should be added as another domain during the interview process. The main objective of this study was to determine the association between grit and happiness among Universiti Teknologi MARA (UiTM) dental students. In addition to that, the prevalence of gritty and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The findings found in similar contexts on the levels of exhaustion reported by dental students provide an alarming perspective, so the use of coping strategies that can be incorporated by university institutions is imperative to avoid academic desertion [ 27 ], as well as also a low motivation of the student about his career and a bad interaction with his patients [ 28 ]. Additionally, regarding the relationship between the dimensions of the BS and the sociodemographic variables, in the present study, statistically significant relationships were found with the marital status variable, with singles reporting higher levels of burnout, possibly due to the fact that students since, they do not have family responsibilities such as children, they tend to overfocus on the professional demands that the career demands of them and dedicate more time to activities such as clinical practices and work.…”
Section: Discussionmentioning
confidence: 99%
“…The findings found in similar contexts on the levels of exhaustion reported by dental students provide an alarming perspective, so the use of coping strategies that can be incorporated by university institutions is imperative to avoid academic desertion [ 27 ], as well as also a low motivation of the student about his career and a bad interaction with his patients [ 28 ]. Additionally, regarding the relationship between the dimensions of the BS and the sociodemographic variables, in the present study, statistically significant relationships were found with the marital status variable, with singles reporting higher levels of burnout, possibly due to the fact that students since, they do not have family responsibilities such as children, they tend to overfocus on the professional demands that the career demands of them and dedicate more time to activities such as clinical practices and work.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the need for dental educators to foster resilience within their student populations, which may occur both prior to matriculation and during dental education. First, resilience may be an admissions criterium of interest, as evidence suggests that such non‐cognitive factors predict academic and clinical success in dental school 26,32–34 . Second, dental students may benefit from concerted attempts to nurture and increase resilience during their professional school career, which is especially needed during the D2 and D3 years.…”
Section: Discussionmentioning
confidence: 99%
“…First, resilience may be an admissions criterium of interest, as evidence suggests that such non-cognitive factors predict academic and clinical success in dental school. 26,[32][33][34] Second, dental students may benefit from concerted attempts to nurture and increase resilience during their professional school career, which is especially needed during the D2 and D3 years. Educational interventions focused on mindfulness, well-being, and selfcare, 20,35 integration of stress management approaches into dental school curricula as other health professions have done, 36 and concerted training efforts for faculty advisors 20 may help support resilience among enrolled dental students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations